Kartlı aktif elektrik enerjisi sayaç sistemi - Etçibaşı, Turgay (Fen Bilimleri Enstitüsü, 1995)
Bu tezde, kartlı eleklik sayacı gerçeklenmiştir. Bu sayaçta simkart kullanıldı ve sayaç NM439? bellek elemanı ile gerçeklendi. Daha sonra tüm sayaçların, merkezi bir bilgisayar ile kontrolünü sağlayan bilgisayar-sayaç haberleşmesi gerçeklendi. Kartlı sayaç sisteminde, tüketici tarafından kullanılacak olan elektrik enerjisinin bedeli, işletmeci kurum tarafından peşin olarak alınır ve bu enerji kredi olarak kartlara yüklenir. Tüketici bu kartlar aracılığı ile sayacını çalıştırabilecektir. Sayaç ayrıca tüketicinin enerjisini otomatik olarak kesebilecektir. Bu amaçla, bilgisayar ve mikroişlemciler kullanılmak suretiyle büyük bir sistemin küçük bir örneği oluşturuldu. Ayrıca çalışmalarda bilgisayar için paralel giriş/çıkış kartı ile mikroişlemci geliştirme kartı tasarlandı.

Identification authorization technology and credit card systems has been developed since 1960 and up to now has been used for many different application. İt is applied personal identification cards, security systems and telephone systems. In mis study, it is adopted to electronic active watthouermeter. Thus, bar code, magnetic stripe cards and smart cards has been examined and compared, to select better one for the watthourmeter. Bar code, magnetic stripe cards and smart cards described in chapter 2. Generally, it is explained their feature, reading and writing method. At first, bar code is studied to apply electronic measuring device. Since bar code is read only coding systems and most commonly used retail application. Two basic types of bar code exist; those that employ only two element widths ( wide and narrow), and those that use multiple elements widths. Some continuous code with multiple element widths are called (njk) codes, where n refers to the number of modules ina character width and k to the number of bars ( and spaces). The total number of possible pattern in an (n^t) code can be determined from the expression: (n-1)! (2k-l)!(n-2k)! Bar code symbol can be printed at low cost with a wide variety of printing techniques, and tehe overall symbol can be uniformly scaled up or down to, suit particular requirements. Bar code is a single dimentional technology^ only the widths of the bars and the spaces contain information....The higth of these elements can be considered as a measure of bar code symbol' s redundancy. Bar code can be thought written form of Morse code. For thirty years, many companies has studied about coding system and today we have a number of coding symbology. E.A.N/13, U.P.C, Codabar, Postnet, interleaved 2 of 5, Code 128 symbologies can be used where the product is needed to label. More and less every product in U.S.A and Europe is labeled using U.P.C and EAN code. A bare code consist of an array of Vntpattern. U.P.C, The most common form of bar code, has been successfully applied to supermarket industries since 1973. U.P.C symbol has ten digits. First five digits indicates manufacturer code and last five digits indicates product code. U.F.C is fixed length, continuous, digital and three element width code Code 39 was the first alpha-numeric symbology to be develop. Widely used, it is now facto nonretail symbology. & is a discrete, self checking, variable length symbology that can readable be printed by a variety of techrmology. Every code 39 character has five bars and four spaces, making a total nine elements. Of these nine elements, three are wide and six are narrow. Code 128 was introduced in 1981 as a very high density alphanumeric symbology. Code 128 has 106 different printed characters. Bar code is an automatic identification technology. It allows real time data to be collected accurately and rapidly. But bar code by itself does not solve problems. The combination of bar code with appropriate hardware and application software creates the potential for improving performance, productivity, and, ultimatry, profitablity. Since a bar code is read only coding sytems, to read a bar code and encode it, we must have scanning devices. There are different types of bar code scanning equipment. To read a messages labeled in a bar code, reading equipment illuminates symbol and collects reflected ligths. This reflected ligths is converted to electrical signals with repects to photo- detector. Obtained analog electrical signals is converted using wave shaper. At last this digital electrical signals sends trough an intelligent device such as computer. ft is oftenry difficult to encode message in a symbol. It must be examined output digital signal to understand what the data in the message. An input device is illustrated in figure a. Ligth source S\. / y a Y M K B O L S y V Ehoto-Detcctor l-*' £ Output Figure a. A simple bar code input device IXIn this application bar code is not suitable. Because we want to use writable and readable cards. As a second, which is the one of important reason, it is expansive device for current watthouer meter. Thus, magnetic stripe cars is examined instead of bar code. Magnetic stripe cards is developed in 60's. And three important standard has been existed since then. These cards are made of P.V.C (polyvinyl chloride) laminated plastic. A stripe of magnetic materials is located along one side of the card and encoded with the required data pattern, on three longitudinal tracks. Track 1 is attributed to the International Air Transport Association (LATA), and contains only alphanumeric information. Track 2 is attributed to the American Bankers Association (ABA), and contains only numeric characters. Track 3 is attributed to the Thrift Industry and contains numeric information which is used intended to be changed or updated. The standard encoding technique is used these card, is known as a two- frequency, coherent phase recording. This method allows for serial encoding of self clocking data on each track. The encoding process is accomplished by converting information into a series of binary bits, and encoding these bits on the tracks of the magnetic stripe as a series of magnetised areas of different polarities. The flux transitions of the bit cell boundaries represents the clocking edges and each intermediate flux transition represents a binary one while its absence represents a binary zero. There must be relative movement between the read/write head and the card when any read or write operation is performed This movement can be accomplished either by moving the card past the head or moving the head over the magnetic stripe. There are many different standards of magnetic cars, ANSI, ISO and BSI are the most important them. Generally, magnetic cars is used in security systems, commercial credit cards. Magnetic cards could be used in this thesis but it is not economical for watthour meters. Read/ write equipment's is expensive, and it is needed external hardware to obtain real information from magnetic cards. Read/ Wite head aleo can be cut of order a* in UBe. I o obtZ reiati ve movanent between head and card, it is needed motorised system that is also expensive for this use.At last smart cards examined to use in mis application and found beet cards for the electrical measuring system. The smart card is new electronic development in the world of credit cards and card-based identification systems. It looks like any other plastic cards but it has imbedded in it a tiny but powerful microcomputer, or non-volatile memory. The basic components of the smart card system are, (he card itself with non-volatile memory such as eeprom or with imbedded microcomputer and associated card reader. The microcomputer is also used in this thesis to measure power and it can be used smart card reader. The access of smart card is easy, and it is not necessary to use coding systems and additional hardware to convert coded messages into binary digital data. For these reason smart card is selected and started practical application. In these watthour meters 8051 microcontroller is used as a main element. 8051 is not best microcomputer for this application, SX6240 and 8096 is better than 8051 but S 1 6240 is the new version of ST62 microcontroller and it is not found in Turkey. For this reason 8051 is used. As describe in chapter three active power is measured using digital technology. A watthour meter has two basic inputs, voltage and current. At first voltage is converted to square wave using wave shaper. This square wave is send to microprocessor to obtain the peak value. At this point current information is send to anolog- digital converter which has sample and hold circuit. An obtained two data is multiplied in microcontroller and found how much energy is consumed. In measurement technique the homonics of current and voltages is ignored. Because of that current and voltage information is filtered by a lowpass filter. It can be used faster anolog-to-digital converters to minimise measurement error. The watthour meter with smart card is designed as a system. Basic elements of this system is watthour meter, smart card and computer. The computer controls all the watthour meters in real time. The communication between computer and electronics watthour meters is accomplished through RS-232 serial interface unit. Turbo C programming language is used. Thus the communication between computer and watthour meter is accomplished. It is not studied on the communication line but it may be telephone line or energy transmission line. It can be suggested as a further study. XIIt is made parallel input/ output interface unit to go faster practical application. This input output card is made for general purpose. Two 8255 parallel input/output elements is used and though other chip can be addressed. The parallel input/output card is used to make 8031 evaluation board. The software program of this card is written by Pascal programming language. Given hardware and software the evaluation board has been made and seen that the speed of transmission of program code. The measurement system with smart card is suggested for Turkey as a new system. In this system illegal usage of energy can be prevented. It can be applied different costs in different times of a day.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: Elektrik enerjisi; Sayaçlar; Electrical energy; Meters